Rewards systems in self-managed organizations - Tenhiälä, Aino; Bonet, Rocío; Nurmi, Niina (My University, 2023)
Organizational forms have continuously evolved alongside broader societal and economic trends. Today there is a quest to reinvent organizations that have a much flatter hierarchy than traditional structures, characterized by increased delegation of decision-making power to lower levels in the organization. These new structures, known as self-managing organizations (SMOs), have abolished manager-subordinate relationships throughout the whole organization. This paper addresses the overriding question, “If there is no traditional managerial hierarchy, how can SMOs ensure that employees will take the actions that are needed to create value for the organization?” It examines an organization that has enjoyed business success while practicing the principles of self-management, focusing on pay transparency, peer-based decisions and horizontal career paths. It presents valuable information about developing and implementing rewards programs for organizations that are giving more decision-making power to their employees.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 16 - Paz, justicia e instituciones sólidas; ODS 10 - Reducción de las desigualdades